The Local Resolution of Cryo-EM Density Maps - Kucukelbir, Alp (2013)
Using local sinusoidal features in a standard statistical testing framework, we propose a definition of local resolution for 3D density maps. The resulting algorithm has no free parameters and may be extended to other imaging modalities. Evaluating the local resolution of single particle reconstructions and sub-tomogram averages shows variable resolution across a 4 to 40Å range.